2020
DOI: 10.1080/01434632.2020.1733586
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic dilemmas and chronic ambivalence in the classroom

Abstract: This special issue brings together papers that discuss how teachers deliberate competing institutional, pedagogical and language ideological imperatives in the multilingual classroom. It does so because research on language-in-education policy often singles out teachers who resist and transform monolingual policies, or those who ignore pupils' multilingual resources. Such accounts usefully highlight the possibility of change or the need for intervention. But they risk overlooking the many occasions where teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In that respect, teachers face continuing dilemmas when it comes to the question of the prestige and value of language varieties in Irish with multiple possible norms available. As Jaspers (2020) argues, teachers can display chronic ambivalence on questions of language. The results from this study and from a previous study with new speaker teachers speak to an ambivalence among teachers of Irish when it comes to their ideologies on variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that respect, teachers face continuing dilemmas when it comes to the question of the prestige and value of language varieties in Irish with multiple possible norms available. As Jaspers (2020) argues, teachers can display chronic ambivalence on questions of language. The results from this study and from a previous study with new speaker teachers speak to an ambivalence among teachers of Irish when it comes to their ideologies on variation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, teachers are shown to appreciate the identity value of so-called non-native speech (Jenkins, 2005), recognise the grammaticality of 'non-standard' varieties and question the prestige status of 'standard' practices (Blake & Cutler, 2003). Alternatively, it is also observed that teachers can display persistently ambivalent and sometimes contradictory ideologies on language and that they continuously negotiate language ideological dilemmas (Jaspers, 2020). Such dilemmas are observed in research on ideologies on variation within named languages, including in research with new speaker teachers of Irish (Ó Murchadha & Flynn, 2018a).…”
Section: Teacher Ideologiesmentioning
confidence: 99%
“…Some studies show that they feel insecure about how to support children's language development (Åkerblom and Harju, 2021;Björk Willén, 2018;Straszer et al, 2020). Other studies show that education in multilingual contexts is bound to convey tensions between norms of monolingualism and multilingualism (Daugaard, 2022;Jaspers, 2022). According to Jaspers (2022), much research either focuses on critical discourse analyses showing that teachers either practise a monolingual norm or 'praise' multilingualism.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies show that education in multilingual contexts is bound to convey tensions between norms of monolingualism and multilingualism (Daugaard, 2022; Jaspers, 2022). According to Jaspers (2022), much research either focuses on critical discourse analyses showing that teachers either practise a monolingual norm or ‘praise’ multilingualism. However, in actual fact, educators are bound to navigate different and often contradictory discourses and language norms brought to school by children, parents and politics etc.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to measures implemented in school aiming to reduce social inequality and differences due to ethnicity, researchers have investigated and explored the effects of mother tongue teaching and bi/multilingual education (Daugaard 2020;Jaspers 2020;Salö et al 2018). However, less attention has been given to how more an informal democratic equality-oriented curriculum puts into play hierarchies and differences, which is what this study aims to explore.…”
Section: Introduction: Establishing School-home Correspondence As a Linguistic Marketmentioning
confidence: 99%